Hot-pressed phosphate glass-ceramic matrix composites containing calcium phosphate particles for nuclear waste encapsulation - Michie, E. M.; Grimes, R. W.; Boccaccini, Aldo R. (Journal of Materials Science, 2008)
Sodium aluminium phosphate (NaAlP) glass-ceramic composites were produced as potential wasteforms for the immobilization of special categories of halide-containing radioactive waste. Sintering conditions for encapsulating a simulated waste (a calcinated mixture of calcium phosphate host and various oxides) in the cold-pressed NaAlP glass-ceramic were first determined and the results were compared with similar samples prepared by hot pressing. In both cases, the conditions aimed to provide a very high-density material, via as low production temperatures as possible, in conjunction with a high waste loading (75 wt.% simulated waste to 25 wt.% glass). It was found that by hot pressing and using a NaAlP glass-ceramic containing 2 mol% B2O3, significantly lower temperatures could be employed compared to the cold pressing and sintering route. The lowest temperature at which a sufficiently dense hot-pressed product was achieved (86% theoretical density), that exhibited mechanical properties similar to those of borosilicate glass (e.g. Young's modulus 67 ± 2 GPa), was 550 °C. This processing temperature is considerably lower than values reported in the literature for similar systems. As such, hot pressing can be considered as a convenient technique for the fabrication of this type of composite for waste encapsulation. © 2008 Springer Science+Business Media, LLC.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.hotpre